Museum Theatre as an Educational Tool: Examples in Serbian Museums - Dragan Kiurski (University of Maribor Press, 2022)
The paper presents museum theatre as an interpretive tool, its theoretical framework, developmental origins, the use of drama in museums in the 20th and 21st centuries, and its pedagogical outcomes. A section of the paper is dedicated to the use of creative drama in museums and its role as an educational model for working with children and young people. Museum performances created in the last ten years in the Matica Srpska Gallery, the Pavle Beljanski Memorial Collection, the Belgrade City Museum, the Kikinda National Museum, the Museum of Vojvodina, and the House of Jevrem Grujić will be mentioned.